TOPOLOGY OPTIMIZATION METHOD BASED ON SIMP-MMC FOR STRUCTURE SIZE PRECISE CONTROL - ZHANG JunFeng; LIAO JingYu; LIU EnHai (Jixie qiangdu)
With the development of structural topology optimization methods, some scholars had proposed strategies to integrate existing topology optimization methods to improve the manufacturability of topology optimization result. Specifically, a topology optimization method combined the Solid Isotropic Material Penalty（SIMP） method and the Moving Morphable Components（MMC） method was proposed. Firstly, the characteristics of power function in SIMP method was used to quickly obtain the main path of force transfer. Secondly, according to the gray-scale elements generated by the SIMP method, an Otsu threshold algorithm was proposed to maximize response of the binary topological structure. On this basis, morphological thought was used to construct a component, whose boundary was the inflection point of the skeleton, then the MMC method was used to complete the optimization to finally achieve the precise control of structure size. By calculating the minimum compliance topology optimization problem of the 2 D and 3 D numerical examples, the optimization results of smooth boundary and precise size of structure are obtained, verifying the effectiveness of proposed method.